Electric trains for reduction of fuel consumption and emissions from the freight transport in Jordan - Charles Sassine (PLoS ONE, 2025)
Transport modes (trucks and diesel trains) used to move phosphate on the corridor connecting Shidiya mine and Aqaba port in Jordan are causing pollutant emissions exceeding global average values. The study proposed the use of electric trains and compared their fuel consumption (FC) and emissions to those of existing transport modes in an attempt to regulate FC and reduce emissions from freight in Jordan. For a more comprehensive view of the three transport modes, FC and emissions were evaluated in various operating conditions in relation to varying speeds, loads, road gradients, and curvatures. Results showed that the three vehicle types were greatly impacted by increasing payloads and speeds. On the other hand, diesel trains were less affected by the road’s curvature and more by its gradient. Electric trains can significantly reduce FC and CO2 emissions at 100% payload and an average speed of 60 km/h compared to trucks and diesel trains. Also, the use of electric trains would maintain CO and N2O emissions at acceptable levels. Regression analysis demonstrated significant negative correlations (R2 > 0.9) between FC and pollutant emissions with increasing payloads for the three vehicles. However, positive correlations were obtained with increasing speeds for diesel (R2 = 0.91) and electric trains (R2 = 0.77). The study offers insights into Jordan’s future strategies for reducing pollution in the transport sector. Based on the findings of the study, drivers may preferably use 100% payload and maintain an average speed of 60 km/h on the selected corridor. Besides, the use of renewable energy sources could potentially further reduce carbon emissions from electric rails.